2013
DOI: 10.1249/mss.0b013e31826e69f0
|View full text |Cite
|
Sign up to set email alerts
|

Macroenvironmental Factors Including GDP per Capita and Physical Activity in Europe

Abstract: Clear differences in national leisure-time physical activity levels throughout Europe may be a consequence of economic development. Lack of economic development of some countries in Europe may make increasing leisure-time physical activity more difficult. Further examination of the link between country GDP per capita and national physical activity levels (across leisure-time, occupational, and transport-related domains) is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…Our hypothesis is that an obesogenic environment would create barriers for weight loss maintenance and may be an intriguing area to investigate. Lastly, the macro‐environment and factors such as gross domestic product per capita and pricing policies have been reported to be associated with weight and weight control behaviours but were not identified in this review on weight loss maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that an obesogenic environment would create barriers for weight loss maintenance and may be an intriguing area to investigate. Lastly, the macro‐environment and factors such as gross domestic product per capita and pricing policies have been reported to be associated with weight and weight control behaviours but were not identified in this review on weight loss maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we employ water consumption, capital, and labor as inputs; sewage as the poor (undesirable) output; and, per capita GDP as the good (desirable) output, as it has a more significant impact on water consumption. This allows for us to get closer to the expected output of water resources based on the environmental Kuznets curve theory [44,45]. Since the DEA method does not directly synthesize the data, the optimal efficiency index of the decision unit has nothing to do with the dimension selection of the input and the output index value.…”
mentioning
confidence: 99%
“…We identified barriers to family‐based physical activity which align with the levels described in Bronfenbrenner's socio‐ecological model . We also found that some issues cross the ecological levels: work patterns and income (exosystem) affect individual isolation and well‐being (microsystem); and the quality of built environments and neighbourhood facilities (mesosystem) was associated with socio‐economic characteristics (macrosystem) . While higher income and better quality environment enabled more physical activity, perceptions and attitudes were common between families in deprived and also affluent neighbourhoods.…”
Section: Discussionmentioning
confidence: 52%
“…Irregular and variable work patterns have been shaped by the expansion of a de‐regulated labour market resulting in a societal change across the macrosystem which has affected lower socio‐economic groups’ disproportionately . Indeed, parents in less affluent areas perceived physical activity as a luxury, and therefore, it was not a regular occurrence. In contrast, parents living in affluent areas reported working mostly regular hours during the week and were therefore able to maintain some form of regular physical activity outside the home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation